2013
DOI: 10.1371/journal.pone.0059491
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Enterococcus faecium and Enterococcus faecalis Strains Isolated from Water and Clinical Samples: Antimicrobial Susceptibility and Genetic Relationships

Abstract: Enterococci are part of the normal intestinal flora in a large number of mammals, and these microbes are currently used as indicators of fecal contamination in water and food for human consumption. These organisms are considered one of the primary causes of nosocomial and environmental infections due to their ability to survive in the environment and to their intrinsic resistance to antimicrobials. The aims of this study were to determine the biochemical patterns and antimicrobial susceptibilities of Enterococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 27 publications
4
41
2
3
Order By: Relevance
“…These results are consistent with previous work by Descheemaeker et al (1999) and Kim et al (2010) where a high level of genetic heterogeneity was observed between E. faecium strains from humans and animals. Similarly Castillo-Rojas et al (2013) also showed that enterococci isolated from humans and those isolated from the environment had high genetic diversity according to PFGE analysis. Thus it can be concluded that in spite of their heterogeneity there are some close relationships, and food might be a potential route for antibiotic resistance transfer to humans.…”
Section: Discussionmentioning
confidence: 86%
“…These results are consistent with previous work by Descheemaeker et al (1999) and Kim et al (2010) where a high level of genetic heterogeneity was observed between E. faecium strains from humans and animals. Similarly Castillo-Rojas et al (2013) also showed that enterococci isolated from humans and those isolated from the environment had high genetic diversity according to PFGE analysis. Thus it can be concluded that in spite of their heterogeneity there are some close relationships, and food might be a potential route for antibiotic resistance transfer to humans.…”
Section: Discussionmentioning
confidence: 86%
“…In our case, all the isolates exhibited typical metabolic reaction to key phenotypic characteristics investigated. For instance, the E. faecalis isolates were able to utilize sorbitol unlike the E. faecium strains, contrary to some reports (Teixeira et al, 1995;Castillo-Rojas et al, 2013). Typically, strains of E. faecium would not produce acid from sorbitol but Day et al (2001) showed that 16 out of 18 E. faecium isolates utilized sorbitol.…”
Section: Discussionmentioning
confidence: 69%
“…Más recientemente, se estudió la relación entre Enterococcus spp. aislados de agua y de pacientes, y se observó que no existía similitud entre ellos y que los aislamientos clínicos presentaron mayor resistencia a los antibióticos que los provenientes del agua (63)(64)(65).…”
Section: Enterococcus Sppunclassified